The Role Model of The Kyai to Improve Religious Awareness of The Santri at Darul A’mal Islamic Boarding School Metro Lampung - Ahmad Fajri; Syahrul Munir (Journal of Research in Islamic Education, 2022)
The aims of this study were to: (1) reveal the exemplary method of boarding school caregivers or Kyai used in increasing the religious awareness of students in the Darul A'mal Islamic boarding school in Metro city, (2) revealing the implementation of exemplary boarding school caregivers in increasing the religious awareness of santri in the darul a'mal Islamic boarding school in metro city, (3) revealing the implications role model for pesantren Kyai in increasing the religious awareness of students in the darul a'mal Islamic boarding school in metro city. To achieve the above objectives, the researcher used a qualitative approach with the type of case study research. Primary data sources are pesantren Kyais, secondary data sources are deputy heads of madrasah diniyah, asatidz or teachers council, homeroom teachers, and students. Data collection techniques used are in-depth interviews, observation and documentation. Data were analyzed by reducing data, displaying data and drawing conclusions. Checking the validity of the data using source triangulation and method triangulation. The results showed that, the reasons for using the exemplary method: santri imitate and imitate the example of the caregiver, the form of direction and guidance reflects the example, the activeness of the caregiver reflects the daily life of the santri. (1). The role model method used: the exemplary method in worship, the exemplary method in tawadhu' and morality, the exemplary method in zuhud, the exemplary method in patience. (2). Implementation of Exemplary: caregivers give an example first, Kyai paid attention to the activity of the ustadz in worship and study, caregivers speak well and behave well. The goals are: taqorrub ilallah, starting with the Kyai giving an example first accompanied by guidance from the slightest thing, practicing istiqomah in carrying out, a form of responsibility as a role model. (3). Implications of exemplary: being uswah or role model in all things, being serious in guiding and directing students, practicing the knowledge gained, based on the hubb (love) of the work being carried out. Implications of exemplary for students: students are easy to direct, students are passionate about worship and study, students are motivated to be the best, students do not feel pressured